Cultural Contestation and Power in the Novel Kubah By Ahmad Tohari - Falah, Fajrul; Salam, Aprinus; Pujiharto, Pujiharto (Allure Journal, 2026)
This study is based on culture ideally should be a noble guideline that unites and elevates human dignity, but in practice it becomes a source of conflict between people .Culture is not a static entity, but rather an arena in which society assigns value and meaning. The purpose of this study is to reveal the contestation of culture and power in the novel Kubah. The theory used is Raymond Williams' Cultural Materialism, which focuses on the analytical framework of dominant, residual, and emergent cultures. This study uses a qualitative method with a textual analysis approach to the novel Kubah. theory. The main objective is to classify and analyze how these three cultures interact, clash, and shape the social landscape as embodied by the characters and main figures in the novel. The steps involved briefly consisted of reading the novel in depth, then classifying words, phrases, sentences, and quoted discourse related to cultural contestation. The data was then analyzed by interpreting the meaning of how the characters and narratives in the novel reflect and maintain their respective identities amid cultural tensions in society. The results of the study show that Karman, as the main character, was alienated by the dominant culture that destroyed communal relations in his village as a result of the events of 1965. However, he found acceptance again through residual culture, namely Javanese traditions and religious values. Karman created new meaning for himself, opening up a space for existence outside the pressures of dominant and residual culture.